Comunità future, Comunità performative - Tomasello, Dario (Mimesis Journal, 2020)
Book review: Playing Inclusion The Performing Arts in the Time of Migrations: Thinking, Creating and Acting Inclusion, Roberta Carpani, Giulia Innocenti Malini (a cura di), «Comunicazioni Sociali Journal Of Media, Performing Arts and Cultural Studies», n.s. 1, 2019